PEMANFAATAN SMART COOL BOX UNTUK MENINGKATKAN KESEGARAN UDANG WINDU PADA PETANI TAMBAK - Arsianti, Rika Wahyuni; Fairul, Fairul (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
Shrimp is an export commodity that contributes foreign exchange to Indonesia. Tarakan City is capable of exporting 13 thousand tons of tiger prawns every year with Japan as the main destination country. However, this shrimp commodity must meet good shrimp quality standards so that it can be exported. The most important factor in keeping shrimp fresh in the cold supply chain is temperature. This study aims to maintain the freshness of shrimp by using internet-based temperature monitoring system technology at shrimp storage posts. In this study the cool box will be maintained so that the temperature does not exceed 50C and has a feature to lower the cool box temperature automatically by flowing cold. The method used in this study was an experiment which was divided into two groups, namely the intervention group and the control group. The intervention group received temperature monitoring with an electronic system while the control group did not receive temperature monitoring. Experimental data will be analyzed by T-test. From the experimental results, it was found that all the shrimp in the intervention group were sold to the shrimp company, while not all were sold in the control group. The T-test results showed 0.07. So it can be concluded that the application of this prototype can minimize damage to shrimp at the storage post.